(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
The current study aims to identify the level of human capital development in the Faculty of Physical Education, and also aims to identify the extent to which human capital development contributes to the development of staff competence in the Faculty of Physical Education. In order to achieve the objectives of the study, the researcher used the descriptive analytical approach, through which he tries to describe the phenomenon under study. The research community included administrative workers in the Faculty of Physical Education at Tishreen University, who numbered /44/ distributed over /13/ divisions and laboratories, while the research sample consisted of individuals who answered the entire questionnaire distributed electronically via the Google Drive link. Where the number of respondents was /26/, which is the number of respondents to the questionnaire. The study concluded that the development of human capital in the Faculty of Physical Education is not at the required level. And that the main problem in the development of human capital in the Faculty of Physical Education lies in the poor training received by the workers in the college. And that workers rely on their training to learn from senior colleagues. The study also concluded that there is a close relationship between human capital development and the perceived self-efficacy of college employees.